2007
DOI: 10.1016/j.jpain.2007.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Cognitions, Coping, and Social Environment Predict Adjustment to Pain in Spinal Cord Injury

Abstract: The current study examined the utility of a biopsychosocial model of chronic pain, and the associations between specific pain-related beliefs, coping, and social support and both mental health and pain interference, in persons with Spinal Cord Injury (SCI) and pain. A total of 157 patients completed surveys assessing physical and psychological functioning, as well as psychosocial, demographic, and injury-related variables. Greater catastrophizing and pain-related beliefs (e.g., the belief that pain signals dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
95
4
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 79 publications
21
95
4
3
Order By: Relevance
“…These focus on the prevalence and course of pain problems and functioning in persons with SCI, 16 the utility of different pain treatments for persons with SCI, 4 the psychometric properties of paininterference measures in persons with SCI, 30 and the utility of a biopsychosocial model of adjustment to pain in SCI. 29 The longitudinal data assessed at 6 months following the initial survey have not yet been reported.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These focus on the prevalence and course of pain problems and functioning in persons with SCI, 16 the utility of different pain treatments for persons with SCI, 4 the psychometric properties of paininterference measures in persons with SCI, 30 and the utility of a biopsychosocial model of adjustment to pain in SCI. 29 The longitudinal data assessed at 6 months following the initial survey have not yet been reported.…”
Section: Methodsmentioning
confidence: 99%
“…In one study, a belief in one's ability to have control over pain was associated with greater mental health, and a number of beliefs were associated with levels of pain interference, such as beliefs that pain signifies damage or that a medical cure exists for pain. 29 Regarding coping responses linked to pain in SCI, two studies in particular have demonstrated that particular coping responses are associated with better mental health, such as greater use of task persistence, 29 coping self-statements, and ignoring pain, 45 while other coping responses are associated with higher levels of pain interference, such as greater use of resting, guarding, and asking for assistance. 29 In addition, social environmental variables, such as perceived social support 29,31 and negative perceived partner responses to pain, 38 have been associated with adjustment.…”
mentioning
confidence: 99%
“…In an experimental setting with 101 healthy volunteers, both active and passive social support given by either a friend or stranger was associated with lower reported levels of pain following a cold pressor task (Brown, 2003). Cross-sectional studies indicated that social support plays a buffering role in the experience of pain, disability and impaired mental health (Kerns et al, 2002;Raichle et al, 2007). Further, Evers and colleagues investigated the predictive role of perceived social support at the time of diagnosis of rheumatoid arthritis.…”
Section: Resilience Resources and Mechanismsmentioning
confidence: 99%
“…Coping and pain Raichle et al 18 looked at coping strategies, social support, pain beliefs and mental health when investigating biopsychosocial aspects of pain. In a sample of 157 patients, they found those with an external LOC and a tendency to catastrophize experienced more pain interference and decreased mental health well-being.…”
Section: Purpose In Lifementioning
confidence: 99%